Utilization of Design Configurators in Order Engineering - Mäkipää, Marko; Paunu, Pasi; Ingalsuo, Timo (International Journal of Industrial Engineering and Management, 2012)
Configurators are essential tools in mass customization. While sales configurators and product configurators have received a fair amount of attention, this study explores a new type configurator for use in order engineering: design configurator. Design configurators can be used to automate order engineering and decrease lead-time for product quotations and customized designs. Thus, they can bring ETO companies closer to mass customization. By determining the requirements for and developing the concept of a design configurator, this paper paves the way for further research on design configurators. Through multiple case studies, the applicability and benefits of design configurators in different industrial contexts are illustrated. Article history: Received (20 November 2012); Revised (01 December 2012); Accepted (06 December 2012)